1986
DOI: 10.2135/cropsci1986.0011183x002600010030x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Photosynthesis and its Correlation with Leaf Area1

Abstract: Comparisons among cultivars of leaf CO2 exchange rate (CER) based on leaf area may be confounded by leaf characteristics not usually accounted for in such comparisons. One such confounding characteristic appears to be leaf size. Correlation coefficients between leaf CER and leaf area (LA) were determined for genotypes of peanut (Arachis hypogaea L.), soybean [Glycine max (L.) Merr.], and sweet potato (Ipomoea batatas L.) and were compared with correlations for other crops reported in the literature. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 0 publications
0
56
0
1
Order By: Relevance
“…Generally, reduction in stomatal conductance (g s ) and E under drought result in higher WUE due to the plant rapidly adjusting water loss through transpiration and absorption of CO 2 through stomatal regulation (Baker et al 2007;Sharkey et al 2007;Tambussi et al 2007). Moreover, Bhagsari and Brown (1986) illustrated that stomatal conductance of fiag leaf positively improves Pn and leaf WUE. Cowan (1988) reported that regulating stomata apertures in leaves can regulate leaf WUE under limited water condition.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, reduction in stomatal conductance (g s ) and E under drought result in higher WUE due to the plant rapidly adjusting water loss through transpiration and absorption of CO 2 through stomatal regulation (Baker et al 2007;Sharkey et al 2007;Tambussi et al 2007). Moreover, Bhagsari and Brown (1986) illustrated that stomatal conductance of fiag leaf positively improves Pn and leaf WUE. Cowan (1988) reported that regulating stomata apertures in leaves can regulate leaf WUE under limited water condition.…”
Section: Introductionmentioning
confidence: 99%
“…Rawson et al (1983) (Dwyer and Stewart 1986), leaf morphology (Bhagsari and Brown 1986) and source and sink strengths (Thiagarajah et al l98l (Vietor etal. 1977;Bhagsari and Brown 1986 …”
mentioning
confidence: 99%
“…2a). The SLW, an important factor determining photosynthetic capacity (Tanaka and Matsushima, 1971;Bhagsari and Brown, 1986), on the other hand, was heavier in BNo than in CONT in all leaves at different positions on a culm (Fig. 2b).…”
Section: Difference Between Bno and Cont In Dmpmentioning
confidence: 98%